Differences in Student Brain Activation from Digital Learning Based on Risk of Digital Media Addiction - GyeongAe Seomun (MDPI AG, 2021)
Although digital media usage is prevalent among middle school students, the safety of digital media-based learning activities for students at risk of digital media addiction is unknown. The goal of this study was to evaluate the differences in students’ brain activity in relation to their risk of digital media addiction. The study was quasi-experimental, with a pre- to post-test control group design. The study participants included 83 middle school students who were engaged in digital learning. We measured their brainwaves to evaluate brain activity using a PolyG-I (LAXTHA Inc.). We found no statistically significant differences in the location of the attention index between the two groups before and after digital learning. However, there were statistically significant differences between the two groups in the P3, P4, and F4 locations of the relaxation index. These results indicate that students at risk of digital media addiction may experience learning difficulties. These results can be used to guide healthcare professionals in developing digital learning programs that are safe for students and to also verify the effects of these programs.